Analysis of the Effect of Polyester and Vinyl Ester Mixture on the Mechanical and Physical Properties of Composite Matrix - Ranto Saputra; Rahmat Fajrul; Murdani (International Journal of Science and Environment (IJSE), 2026)
The application of pure polyester resin as a polymer composite matrix is often limited by its inherent brittleness and low impact resistance. This study investigates the effects of incorporating vinyl ester resin into a polyester matrix at various weight ratios (100:0, 90:10, 80:20, 70:30, 60:40, and 50:50) using 1 vol% Methyl Ethyl Ketone Peroxide (MEKP) catalyst. Physical properties (density and porosity) were evaluated via Archimedes' fluid displacement principle, while impact toughness was characterized using Charpy impact testing according to ASTM D6110 standards. Fractographic and phase morphology analyses were conducted using Scanning Electron Microscopy (SEM). The experimental results demonstrate a progressive increase in impact toughness with higher vinyl ester concentrations, rising from 2.79 kJ/m² in pure polyester to a maximum value of 6.51 kJ/m² in the 50:50 blend, representing an improvement of approximately 133%. Physical evaluation showed a minor decrease in density from 1.182 g/cm³ to 1.155 g/cm³ and a slight increase in porosity up to 1.45%, which remained well below critical structural limits. SEM micrographs revealed a clear transition from a smooth, flat, brittle cleavage fracture in pure polyester to a rough, ductile-dominated fracture surface characterized by deep tear ridges and plastic deformation in higher vinyl ester blends, with no phase separation observed. Overall, the 50% polyester and 50% vinyl ester blend formulation provides the optimal combination of impact toughness, structural integrity, and phase compatibility for composite matrix applications.